Restenosis pathophysiological mechanisms and genetic markers after percutaneous coronary interventions - Yu. A. Shuvalova; A. N. Meshkov; A. I. Kaminny; G. F. Piksina; V. V. Kukharchuk (Кардиоваскулярная терапия и профилактика)
Coronary restenosis remains the main problem for effectiveness of percutaneous transluminal coronary angioplasty (PCA) and coronary stenting (CS). The aim of this review is to analyze pathogenetic mechanisms of coronary restenosis after PCA and CS, as well as various polymorphisms of relevant candidate genes as potential genetic markers of post‑PCA and post‑CS restenosis. Both pathophysiological mechanisms and genetic basis are different for stent restenosis and post‑PCA, stent‑free restenosis. There are genes, which could be used as genetic markers of stent restenosis risk. For PCA restenosis risk, there are genes, also used as genetic markers. Genetic testing before percutaneous coronary interventions could identify patients with high restenosis risk, that, combined with new pharmaceutical approaches, will decrease coronary restenosis rates after PCA and CS.